Illustrated Pediatric Dentistry - Part 2 - Damle, Satyawan; Kalaskar, Ritesh; Sakhare, Dhanashree (Bentham Science Publishers, 2023)
Illustrated Pediatric Dentistry is intended to be a text book for enhancing the knowledge and understanding of paediatric dentistry amongst undergraduate and postgraduate students. This textbook is updated with the latest information on techniques employed in paediatric dentistry. Chapters in this part cover primary paediatric dentistry, its clinical aspects, preventive dentistry, and information about the latest trends prevalent in this specialty field of dentistry. The text will equip readers with the knowledge suited to the changing environment of this vital domain. The editor of this textbook has over forty-four years of teaching experience in paediatric dentistry and is able to successfully impart a broad perspective of the subject through the book's contents. This textbook is the amalgamation of the experience and knowledge of various subject experts that command a high international reputation. Part 2 covers orofacial swelling, pediatric space management, interceptive orthodontics and myofunctional therapy, gingival and periodontal diseases, oral hygiene, minimum intervention dentistry (MID), molar incisor hypoplasia (MIH), restorative dentistry, and oral examination and diagnostic aids used in pediatric dentistry. Key Features: - The 15, structured chapters present the latest trends in paediatric dentistry - The book content is illustrated with quality clinical images, - Chapters cover contemporary concepts of problems experienced when treating multiple dental disorders in young patients - Contributions from subject experts present distinct clinical expertise and a unique style of imparting important current knowledge to budding professionals - The book includes modern and current state-of-the-art techniques used in the clinic - Topic outlines throughout the book will greatly help readers to quickly locate and review the content. Contents of the book are very well structured and presented in a lucid manner, making it easy to understand.